CHARACTERISTICS OF ANTERIOR URETHRAL STRICTURE AT TERTIARY HOSPITAL IN INDONESIA, 2022–2024 - Abdul Rahman; Ahmad Agil (The International Journal of Medical Science and Health Research, 2026)
Background: Anterior urethral stricture is a narrowing of the urethra due to fibrosis, leading to lower urinary tract obstruction and significantly affecting patients' quality of life. Although common, data on its characteristics in Indonesia remain scarce. Objective: To describe the clinical profile, etiological distribution, treatment modalities, and postoperative complications of anterior urethral stricture at Hasan Sadikin General Hospital Bandung. Methods: A descriptive observational study with a cross-sectional design was conducted using medical records of male patients with anterior urethral stricture treated at the Department of Urology, Hasan Sadikin General Hospital Bandung, between 2022 and 2024. Data were analyzed descriptively. Results: A total of 159 male patients were included. The mean age was 52.15 ± 17.90 years. The most common clinical presentation was urinary retention (70.45%). The bulbar urethra was the most frequent stricture location (47.79%), with the majority of strictures being less than 2 cm in length (82.38%). The predominant etiology was iatrogenic, particularly post-transurethral surgery (38.36%), followed by trauma (37.10%). The most frequently performed treatment was Excision Primary Anastomosis (41.50%), followed by Direct Visual Internal Urethrotomy (28.30%). Postoperative complications occurred in 22.64% of patients. Conclusion Anterior urethral stricture at this Indonesian tertiary referral center primarily affects middle-aged to elderly men, with urinary retention as the most common presentation and the bulbar urethra as the typical site. Iatrogenic causes dominate, underscoring the need for preventive measures during endoscopic procedures. EPA remains the mainstay treatment for short bulbar strictures.